2014
DOI: 10.2500/aap.2014.35.3742
|View full text |Cite
|
Sign up to set email alerts
|

The role of Mycoplasma pneumoniae infection in the initial onset and exacerbations of asthma

Abstract: Asthma is a disease in which airway hyperresponsiveness, increased airway contraction, and airway secretion occur as a result of allergic airway inflammation. Mycoplasma infections are well known to exacerbate asthma pathology as well as to cause the onset of asthma itself. Mechanisms of airway epithelial injury, activation of innate immunity, or increased Th2-dominant immune responses caused by community-acquired distress syndrome toxin (CARDSTx) or diacylated lipoprotein have been reported in exacerbations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Tagliabue et al 14 found an obstructed airway among patients with M pneumoniae infection, regardless of combined therapy with antibiotics and steroids. Collectively, these findings imply that M pneumoniae 1 increases the relationship between airway infections and incident asthma, 33,41 especially in patients with a severe M pneumoniae infection. M pneumoniae infection seems to be a precipitating factor for asthma development in predisposed persons.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Tagliabue et al 14 found an obstructed airway among patients with M pneumoniae infection, regardless of combined therapy with antibiotics and steroids. Collectively, these findings imply that M pneumoniae 1 increases the relationship between airway infections and incident asthma, 33,41 especially in patients with a severe M pneumoniae infection. M pneumoniae infection seems to be a precipitating factor for asthma development in predisposed persons.…”
Section: Discussionmentioning
confidence: 81%
“…7,8 Collectively, the findings imply that M pneumoniae infection is an independent factor that can lead to incident asthma. 33 During the 2-year follow-up period, the aHR of asthma was highest among those patients with M pneumoniae within the first 6 months, and it decreased in both cohorts at or after the 2-year duration. 21 Severe inflammation in the initial stage of M pneumoniae infection implies that the acute infection is a predisposing factor of an asthma attack episode during the less than 6-month period.…”
Section: Discussionmentioning
confidence: 83%
“…[20][21][22] The prevalent generation of Th2 immune responses and inflammation may promote pediatric asthma during M. pneumoniae infection. 23 Total and specific IgE responses have been described during M. pneumoniae respiratory infections, as well as in several viral and bacterial airways infections. 24,25 However, despite atopy is considered a risk factor to develop asthma in children, actually there is no evidence supporting a prominent specific IgE response during respiratory infections due to M. pneumoniae or in the complicated clinical forms.…”
Section: Discussionmentioning
confidence: 99%
“…Host immune factors may influence the outcome of infection, and previous findings showed that asthmatic children were lacking in cellular and humoral responses to MP infection (17,18). MP may infect the upper and lower respiratory tract, causing pneumonia or bronchitis, and may be involved in the initiation and recurrence of asthma exacerbations (19,20). It has been suggested that MP infection leads to changes of a variety of serum immune parameters, such as MP immunoglobulin M (MP-IgM), MP immunoglobulin E (MP-IgE), interleukin-18, eosinophils (EOS) count and others (2123).…”
Section: Introductionmentioning
confidence: 99%